New data on the distribution of chigger mites (Acariformes: Trombiculidae) associated with small mammals in Vietnam - Antonovskaia, A.a.; Balakirev, A.e.; Lopatina, Y.v. (Zootaxa, 2023)
The study of chigger mites of Vietnam is based on the material collected during fieldworks in 2011–2019 and examination of small mammal samples deposited in museum collections. A total 59 small mammals species were examined (49 species of Rodentia, 8 species of Eulipotyphla, and 2 species of Scandentia). On them, 79 species of chigger mites were collected, of which 44 species are recorded in Vietnam for the first time. Thus, the list of chigger mite species reported in Vietnam has been extended to 122 species belonging to 16 genera and 3 subfamilies. Most recorded species belong to the genera Leptotrombidium and Walchia. New hosts have been recorded for 48 trombiculid species. The study showed that the diversity of trombiculids of various regions of Vietnam has been studied unevenly.